Support of Characteristics, Physical Environmental and Psychological On Quality Of Life Of Patients With DM Type II - Malik, Fivit Febriani; Amiruddin, Ridwan; Wahiduddin, Wahiduddin; Maria, Ida Leida; Hasan, Nurzakiah; Rivai, Fridawaty; Haerani, Haerani (International Journal of Statistics in Medical Research, 2024)
Background: Diabetes mellitus is one of the diseases that ranks high in the list of non-communicable diseases in Indonesia. Factors that can affect quality of life such as physical environment and psychological. Objective: This study aims to examine the relationship between characteristic, physical environment and psychological on quality of life of type II diabetes mellitus patients at the Barombong Public Health Center, Makkasar City. Methodology: This study is a quantitative research with an analytical observational approach using a cross-sectional design. The population size in this study is 578 individuals, sample calculation using the WHO formula yielded a sample size of 385 individuals with predefined exclusion an inclusion criteria. The sampling technique employed is simple random sampling (SRS), and the hypothesis test used is chi-square. Results: Bivariate statistical analysis shows that there is a relationship between quality of life and age (p=0,000), duration of illness (p=0,000), temperature (p=0,000), noise (p=0,000), positive feelings (p=0,000), thinking, learning, and concentration (p=0,000), self-esteem (p=0,000), while variables that are not associated with quality of life are gender (p=0,111), marital status (p=0,228) and social support (p=0,645). Based on logistic regression analysis, it was found that the factors that most influence quality of life are duration of illness (p=0,000) and positive feelings (p=0,000). Conclusion: Length of suffering and positive feelings are the most dominant variables associated with quality of life with a probability level of 99.8%.